Positioning the battle for your mind - Ries, Al.; Trout, Jack. (New York London McGraw-Hill Companies, Inc., 2001)
This book has been written about a new approach to communication called positioning. And most of the examples are from the most difficult of all forms of communication--advertising. A form of communication that, from the point of view of the problem, is held in low esteem. Advertising is, for the most part, unwanted and unliked. In some cases, advertising is thoroughly detested.

To many intellectuals, advertising is selling your soul to corporate America--a subject not worthy of serious study.

In spite of its reputation, or perhaps because of it, the field of advertising is a superb testing ground for theories of communication. If it works with advertising, most likely it will work in politics, religion, or any other activity that requires mass communication.

So the examples in this book could just as well have been taken from the field of politics, war, business, or even the science of chasing the opposite sex. Or any form of human activity which involves influencing the minds of other people. Whether you want to promote a car, a cola, a computer, a candidate, or your own career.

Positioning is a concept that has changed the nature of advertising, a concept so simple, people have difficulty understanding how powerful it is.

Every successful politician practices positioning. So do Procter & Gamble and Johnson & Johnson.
What positioning is all about -- The assault on the mind -- Getting into the mind -- Those little ladders in your head -- You can't get there from here -- Positioning of a leader -- Positioning of a follower -- Repositioning the competition -- The power of the name -- The no-name trap -- The free-ride trap -- The line-extension trap -- When line extension can work -- Positioning a company: xerox -- Positioning a country: Belgium -- Positioning an island: Jamaica -- Positioning a product: milk duds -- Positioning a service: mailgram -- Positioning a long island bank -- Positioning a New Jersey bank -- Positioning a ski resort: Stowe -- positioning the catholic church -- Positioning yourself and your career -- Positioning your business -- Playing the positioning game
"How to be seen and heard in the overcrowded marketplace"--Cover.
Includes index.
Donated by Prof. Michelle Roxas
Keywords: Positioning (Advertising)